Entomological studies on the impact of a small-scale irrigation scheme on malaria transmission around Ziway, Ethiopia - Kibret, S.; Petros, B.; Boelee, Eline; Tekie, H. (2008)
To evaluate the impact of a small-scale irrigation scheme on the level of malaria transmission in a semi-arid area, entomological studies were conducted in Zeway area, Central Ethiopia. Larval and adult anophelines were sampled during the dry and short-rainy seasons from irrigated and non-irrigated villages. Overall, significantly higher density of Anopheles larvae were found during the dry season in the irrigated village (Mean = 38.3 larvae/100 dips) than the non-irrigated village (7.4 larvae/100 dips). Canal leakage pools, irrigated fields and irrigation canals were the major sources of Anopheles mosquitoes. Larval and adult Anopheles pharoensis and An. arabiensis, principal malaria vectors in Ethiopia, were more abundant in the irrigated village than the non-irrigated village throughout the study period. Hourly light trap catches revealed that peak indoor and outdoor biting activities of An. arabiensis and An. pharoensis occurred during the early period of the night before the local inhabitants retire to bed. The majority of blood-engorged An. arabiensis (0.78) and An. pharoensis (0.69) had fed on humans, suggesting that their highly anthropophilic nature in Zeway area. Plasmodium falciparum infection rates of 1.02% and 0.54% were determined for An. arabiensis and An. pharoensis, respectively, in the irrigated village. This study demonstrated that due to poorly maintained irrigation structures, the irrigation scheme created conducive breeding grounds for malaria vector species, particularly during the dry season. Consequently, the period of malaria transmission might possibly extend from seasonal to year-round, involving the dry season. Proper water management coupled with environmental management such as source reduction could reduce vector abundance and hence malaria transmission in the irrigation schemes.